2003
DOI: 10.1152/japplphysiol.00951.2002
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in effects of exercise training on contractile and biochemical properties of rat cardiac myocytes

Abstract: Myocardial function is enhanced by endurance exercise training, but the cellular mechanisms underlying this improved function remain unclear. A number of studies have shown that the characteristics of cardiac myocytes vary across the width of the ventricular wall. We have previously shown that endurance exercise training alters the Ca2+ sensitivity of tension as well as contractile protein isoform expression in rat cardiac myocytes. We tested the hypothesis that these effects of training are not uniform across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 40 publications
(92 reference statements)
5
19
0
Order By: Relevance
“…We observed that the ovariectomy associated with exercise training in wild and / or dyslipidemic mice increased cross-sectional area of cardiomyocytes (AST) and the medium nuclear volume (V), suggesting myocyte hypertrophy. Similar results 18,19 were observed in ovariectomized and trained rats, and in metabolic syndrome animals 15 subject only to physical training. The hypertrophy of the heart muscle is an attempt to heart adaptation to the overload work 11,20,21 .…”
Section: Discussionsupporting
confidence: 80%
“…We observed that the ovariectomy associated with exercise training in wild and / or dyslipidemic mice increased cross-sectional area of cardiomyocytes (AST) and the medium nuclear volume (V), suggesting myocyte hypertrophy. Similar results 18,19 were observed in ovariectomized and trained rats, and in metabolic syndrome animals 15 subject only to physical training. The hypertrophy of the heart muscle is an attempt to heart adaptation to the overload work 11,20,21 .…”
Section: Discussionsupporting
confidence: 80%
“…28 Another hypothesis is an impaired muscle oxygenation. [29][30][31] Besides, similarly to baseline analysis, there was an increase in the relaxation time in the PSD96.…”
Section: Discussionmentioning
confidence: 99%
“…However, data on the literature have shown that regular exercise has an impact on length-tension relationship of left ventricular cardiomyocytes, thereby increasing contraction force. [29][30][31] On the other hand, length-DT relationship was decreased in animals subjected to aerobic exercise, suggesting no effect of this type of exercise on attenuating this parameter. 25 Post-rest potentiation of electrical stimulations allows to indirectly determine the balance between the processes of Ca +2 reuptake, storage and release, controlled by sarcoplasmic reticulum, and intracellular Ca +2 release through the sarcolemma.…”
Section: Discussionmentioning
confidence: 99%
“…These accumulated data imply the importance of nucleotide sequences other than the classical E-box for transcriptional regulation by Mitf. Expression of MLC-1a causes a pronounced positive inotropic effect (39) and is associated with increased Ca 2ϩ sensitivity (6). Moreover, MLC-1a expression is augmented following myocardial infarction (25), in dilated cardiomyopathy (22), and under hemodynamic overload conditions (26).…”
Section: Discussionmentioning
confidence: 99%